Sikap Ahlus Sunnah Terhadap Pemerintah Republik Indonesia Yang Berideologi Pancasila - Prima Ayu Rizqi Mahanani; Umi Hanik (Postgraduate State Islamic Institute (IAIN) Metro, 2018)
Ahlus sunnah has a special identity compared to other groups with various characteristics, morals, thoughts, appearance, and life. They simply refer to the Koran and the assunnah and abandon everything that excludes it. Trying to leave a case that causes disputes and debates in religious affairs and outside of religion so that they can be religious in a kaffah manner. This study aims to find out the true thinking ahlus sunnah in facing the reality of life in multicultural Indonesia and want to express their attitude towards the Indonesian government that ideology Pancasila. Therefore, a qualitative approach is used with in-depth interview method to salafi leader in Kediri city, that is in Pondok Pesantren Imam Muslim. The result of descriptive analysis shows ahlus sunnah understanding that far from the values of radicalism and anarchism, even acts of terrorism. Their da'wah is more to improve the people in matters of aqidah, worship, morals and invites people to unity derived from the Qur'an and the sunnah of the Prophet. There is a correspondence between morality of salafush shalih and the values contained in Pancasila and obliging its congregation to obey the government in all its laws, laws, laws, policies and programs.